Cost-effectiveness of optimized adherence to prevention guidelines in European patients with coronary heart disease: Results from the EUROASPIRE IV survey. (1st December 2018) - De Smedt, Delphine; Annemans, Lieven; De Backer, Guy; Kotseva, Kornelia; Rydèn, Lars; Wood, David; Amouyel, Philippe; Bruthans, Jan; Cifkova, Renata; De Sutter, Johan; Dolzhenko, Marina; Erglis, Andrejs; et al.
Abstract: Background: This study aims to assess the cost-effectiveness of optimized guideline adherence in patients with a history of coronary heart disease. Methods: An individual-based decision tree model was developed using the SMART risk score tool which estimates the 10-year risk for recurrent vascular events in patients with manifest cardiovascular disease (CVD). Analyses were based on the EUROASPIRE IV survey. Outcomes were expressed as an incremental cost-effectiveness ratio (ICER). Results: Data from 4663 patients from 13 European countries were included in the analyses. The mean estimated 10-year risk for a recurrent vascular event decreased from 20.13% to 18.61% after optimized guideline adherence. Overall, an ICER of 52, 968€/QALY was calculated. The ICER lowered to 29, 093€/QALY when only considering high-risk patients (≥20%) with decreasing ICERs in higher risk patients. Also, a dose-response relationship was seen with lower ICERs in older patients and in those patients with higher risk reductions. A less stringent LDL target (<2.5 mmol/L vs. <1.8 mmol/L) lowered the ICER to 32, 591€/QALY and intensifying cholesterol treatment in high-risk patients (≥20%) instead of high-cholesterol patients lowered the ICER to 28, 064€/QALY. An alternative method, applying risk reductions to the CVD events instead of applying risk reductions to the risk factors lowered the ICER to 31, 509€/QALY. Conclusion: Depending on the method used better or worse ICERs were found. In addition, optimized guidelines adherence is more cost-effective in higher risk patients, in patients with higher risk reductions and when using a less strict LDL-C target. Current analyses advice to maximize guidelines adherence in particular patient subgroups. Highlights: Guidelines adherence is more cost-effective in higher risk patients. The room for improvement is a key driver of the ICER. Depending on the method used better or worse outcomes were found.